2011
DOI: 10.1097/sih.0b013e318224bdde
|View full text |Cite
|
Sign up to set email alerts
|

Integrated In-Situ Simulation Using Redirected Faculty Educational Time to Minimize Costs

Abstract: This report demonstrates the feasibility of implementing an in situ simulation program using minimal permanent institutional space and cost-neutral redirected faculty time. This type of programmatic structure is conducive to short- and medium-term growth, is well received by participants, and allows for substantial cost savings. Future work will be needed to determine what growth limitations are inherent in this staffing and structural model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 22 publications
1
28
0
Order By: Relevance
“…Although several studies show that successful ISS can take place with at a minimal cost compared to simulation centres [19, 29, 6668], ISS can require extra space for clinical activities, which may mean increased costs.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies show that successful ISS can take place with at a minimal cost compared to simulation centres [19, 29, 6668], ISS can require extra space for clinical activities, which may mean increased costs.…”
Section: Discussionmentioning
confidence: 99%
“…An advantage of ISS is that it is conducted in the real workplace, thus making it possible to train staff and also identify systemic weaknesses, which in turn forms the basis for required organisational changes 15–18. Some have argued that ISS is more feasible and cost saving compared with traditional simulation conducted in simulation centres 19 20. Some studies concluded that ISS is met with widespread acceptance among participants and has resulted in a collaborative approach to patient safety 14 19 21 22…”
Section: Introductionmentioning
confidence: 99%
“…As highlighted in this review, there is great variation in the approach to the utilization of simulation and curricular design across institutions. Although the majority of pediatric studies have used simulation centers or in situ simulation programs for assessment of resident performance and procedural proficiency, 23,27,28,33,36,43,48,49,57,58 alternative tech niques such as the crea tion of a www.hospitalpediatrics.org formal mock code curriculum 24,37,41,59 and just-in-time procedural training as part of the PICU rotation 20,35 have also been performed. Although some of these curriculum designs have achieved meaningful results, there is a lack of consensus for the ideal approach to simulation implementation into a pediatric residency program.…”
Section: Discussionmentioning
confidence: 99%